Reversible Martensitic Phase Transition in Yttrium-Stabilized ZrO2 Nanopowders by Adsorption of Water - Elmar B. Asgerov; Anatoly I. Beskrovnyy; Nelya V. Doroshkevich; Carmen Mita; Diana M. Mardare; Dan Chicea; Mihaela D. Lazar; Alisa A. Tatarinova; Sergiy I. Lyubchyk; Svitlana B. Lyubchyk; Andriy I. Lyubchyk; Alexander S. Doroshkevich (Nanomaterials, 2022)
The present study was aimed at revealing the influence of the mechanical stress induced by water molecule adsorption on the composition of crystalline phases in the ZrO2 + 3 mol% Y2O3-nanoparticles. Three basic methods were used to determine the phase transition: neutron diffraction, Raman microspectroscopic scanning, and X-ray diffraction. The fact of reversible phase-structural β → α transformation and the simultaneous presence of two polymorphic structural modifications (β is the phase of the tetragonal syngony and α of monoclinic syngony in nanosized particles (9 nm)) under normal physical conditions was established by these methods. An assumption was made regarding the connection of the physical mechanism of transformation of the extremely nonequilibrium surface of nanoparticles with electronic exchange of the material of the near-surface layer of nanoparticles with the adsorption layer through donor–acceptor interaction. The principal possibility of creating direct-acting hydroelectric converters based on nanoscale YSZ (Yttria-Stabilized Zirconia) systems due to the reversible character of the considered effect was shown.